L’Educatore Digitale in sanità - Bellini, Claudia (FrancoAngeli, 2023)
More than two decades have passed since the start of the national programme of Continuing Education in Medicine and, during this time, training for health professionals has become a pathway co-constructed by a plurality of roles involved in the design and implementation of an effective training experience. In this regard, this text describes the characteristics of and connections between three elements that are well known, yet sometimes made explicit in a fragmentary manner: the context (of continuing healthcare training), the action (of designing it), and the support staff. In particular, the emerging role of the Digital Educator is presented in its function of support and co-design in the specific field of e-learning in healthcare. their competences are articulated in this book in seven tips, in order to guide the actions of future Digital Educators who for the first time find themselves co-designing online trainings in the healthcare sector and, at the same time, support the knowledge of professionals who are already working in the training offices of the AUSL.